SPIRITUAL DIMENSION OF THE NEW PARADIGM OF THE GLOBAL DEVELOPMENT IN THE FUTUROLOGY OF THE CLUB OF ROME - Shorina, Тetiana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Анотація. The article deals with the problem of substantiating a new paradigm of global development in the studies of the Club of Rome, namely the paradigm of sustainable or holistic development. The philosophical and moral framework of the new social paradigm is studied. The new social paradigm frameworkis embodied in the strategy of "world equilibrium for mankind" (D. Meadows), the doctrine of "new humanism" (A. Peccei) and "new enlightenment" (E. Weizsäcker, A. Wijkman). Keywords: futurology, holism, new global paradigm, global problems of mankind, world order, financial capitalism, new enlightenment, new humanism, Club of Rome, sustainable development, world in crisis.